Effect and mechanism of acidic aggregate surface silane modification on water stability of asphalt mixture. Issue 7 (3rd July 2021) - Yang, Ming; Huang, Tuo; Lv, Songtao; Zheng, Jianlong
Abstract : This study assessed the water stability of asphalt mixtures incorporating granite aggregates. A silane coupling agent was adopted to modify the surface of the granite aggregates, and scanning electron microscopy, contact angle measurements, Fourier transform infrared spectroscopy, and X-ray fluorescence were used to analyze the micro- and meso-characteristics of the aggregates. Effects of the silane treatment on the water stability of the mixtures were further evaluated by immersion and vacuum saturation Marshall tests and freeze–thaw splitting tests. The results indicated that the silane coupling agent had grafted onto the aggregate surface via chemical interactions, resulting in obviously raised contact angles and greatly reduced hydrophilicity. Additionally, the deposited organic film also reacted with the asphalt and formed a tighter bonding interface between the asphalt and aggregates, resulting in an asphalt mixture with a higher residual stability and splitting tension strength ratio when under environmental stress.